Gambaran pemberian ASI esklusif dan susu formula terhadap kejadian obesitas balita di salatiga - Hirkanus Fransiskus Humune; Kristiawan P.A Nugroho P.A Nugroho; Rifatolistia Tampubolon (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: National coverage of exclusive breastfeeding in infants 0-6 months, foods that are often given when a newborn baby, such as formula milk, honey, and water which includes non-formula milk, honey, sugar water, bananas smooth, the sweet, and fine bubu. These foods are called prelacteal foods, these foods can be very dangerous if given too early to babies because these foods do not contain enzymes so that absorption in food will always depend on the enzymes found in the baby's milk (Ministry of Health Republic of Indonesia 2015). On Government Regulation Number 33 In 2012 every Indonesian citizen with a healthy condition, is required to give exclusive breastfeeding to her baby since she was born for six months without adding and or replacing with other food and drinks. The aim is to describe breastfeeding and formula milk in the incidence of obesity in children under five in Salatiga. Method In this research the research method used is quantitative (descriptive) research method which will be carried out in August - October 2019. Population is a group of elements or elements that can be in the form of humans or individuals, animals, plants, institutions or institutions, groups , documents, events, things, symptoms, or concepts that form the object of research, the population in this study are mothers who have obese toddlers in Salatiga. Discussion: Based on the results above, most respondents understood that breastfeeding for infants was an important thing to do, mainly through the socialization of exclusive breastfeeding programs delivered by nutrition workers and cadres in local health services, both at the Puskesmas and Posyandu. Mothers and families are always reminded by nutrition workers and cadres to routinely breastfeed babies and infants, especially exclusive breastfeeding at least until the age of 6 months. The respondents said that exclusive breastfeeding continued until the age of 6 months, then continued with formula feeding. Breastfeeding for the first time plays a role in the provision of nutrition that begins at the time of gestation and eating behavior begins to be conditioned and trained early in life (Afifatun, 2014).